Study on inpatient expenses and cost control strategies for breast cancer patients based on Diagnosis-Intervention Packet - Yue, Limin; Pan, Zhengchen; Chen, Wujun (Frontiers in Public Health, 2025)
AimTo provide reference information for reducing disease burden and promoting medical service. The inpatient expenses of breast cancer patients in a top-three public hospital in Zhengzhou under the background of Diagnosis-Intervention Packet (DIP) payment reform were analyzed, and corresponding cost control strategies were proposed.MethodsIn this study, 4,590 patients (3,311 before reform and 1,279 after reform) were finally included in this study. Student's t-test was used to compare the means of two samples. Chi-square test was used for the comparison of rates. The influencing factors of profit of the patients after reform were analyzed by binary logistic regression.ResultsPost-reform data revealed a significant reduction in medication costs and examination fees (P < 0.05), contributing to lower overall hospitalization expenses. The profit ratio of c50.9_86 (c50.9_86.0603: chemotherapy pump implantation surgery for unspecified breast malignant tumors) group was the highest, about 63.2%, and the loss ratio of c50.9_99 (c50.9_99.2503: intravenous injection of chemotherapy drugs for unspecified breast malignant tumors) group was the highest, about 66.7%. The length of hospital stay was the protective factor of profit, whereas the score of disease and employee insurance were the risk factors of profit.ConclusionThe DIP reform significantly reduced medication costs outside of surgery. Under the DIP payment mode reform policy, hospitals should strengthen the awareness of cost control and reduce medical costs, optimize the score of disease and group setting, pay attention to optimize disease structure and ensure fair access to treatment for patients.